2018
DOI: 10.1016/j.electstud.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Voting and satisfaction with democracy in flexible-list PR

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…One of the most common measures of public opinion administered in social science surveys is "satisfaction with democracy" (SWD). This measure is widely used 1 within social science research as an indicator of political support and the political health of a democratic society (Aarts and Thomassen 2008;Anderson and Guillory 1997;Bernauer and Vatter 2012;Bol et al 2018;Dassonneville and McAllister 2020;Grönlund and Setaïa 2007;Karp, Banducci, and Bowler 2003;Reher 2015;Zmerli, Newton, and Montero 2007). In media and popular discourse, a lack of satisfaction with political institutions and the elites which occupy them has been cited as a cause and consequence of the rise of challenger parties, the stupefaction of status quo institutions, and the catalyst of discrete events like the "Brexit" vote and Donald Trump's presidency (Kaltwasser and Van Hauwaert 2020;Knot 2016;McCall 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common measures of public opinion administered in social science surveys is "satisfaction with democracy" (SWD). This measure is widely used 1 within social science research as an indicator of political support and the political health of a democratic society (Aarts and Thomassen 2008;Anderson and Guillory 1997;Bernauer and Vatter 2012;Bol et al 2018;Dassonneville and McAllister 2020;Grönlund and Setaïa 2007;Karp, Banducci, and Bowler 2003;Reher 2015;Zmerli, Newton, and Montero 2007). In media and popular discourse, a lack of satisfaction with political institutions and the elites which occupy them has been cited as a cause and consequence of the rise of challenger parties, the stupefaction of status quo institutions, and the catalyst of discrete events like the "Brexit" vote and Donald Trump's presidency (Kaltwasser and Van Hauwaert 2020;Knot 2016;McCall 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A reason is probably that preference-voting results are quite influential, even beyond the election of parliamentary representatives. In many countries, a candidate who receives a high preference score is also likely to become minister or be appointed to a leading position within the party (André et al 2017;Bol et al 2018;Folke, Persson, and Rickne 2016;Meriläinen and Tukiainen 2018).…”
Section: Preference Voting In the Literaturementioning
confidence: 99%
“…There is limited research on the impact of more particular institutional features. Based on panel survey data from Belgium, Bol and coauthors concluded that 'casting a preference vote for a winning candidate [in a flexible-list PR system] makes little difference, as party-list voters are those with the largest increase in satisfaction with democracy' (Bol et al, 2018).…”
Section: Systemic Differences In the Winner-loser Gapmentioning
confidence: 99%
“…Many studies document the existence of a winner-loser gap in satisfaction with democracy (inter alia Blais et al, 2017;Farrer & Zingher, 2019;Loveless, 2020). While it is still unclear what changes open up the gap -whether it is winners increasing their satisfaction, or losers decreasing it, or both (Esaiasson, 2011;Hansen et al, 2019;van der Meer & Steenvoorden, 2018), differences between election winners and losers are found across different empirical contexts and with different research designs, including panel survey data (Bol et al, 2018;Gärtner et al, 2020). Some of the mechanisms that underpin the winner-loser gap in satisfaction with democracy are rather general.…”
Section: Introductionmentioning
confidence: 99%